2020
DOI: 10.1021/acs.energyfuels.9b04533
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Reduction Treatments of Mo/Sepiolite Catalyst on Lignin Depolymerization under Supercritical Ethanol

Abstract: Depolymerization of lignin to produce high yield lignin oil is one of the prospective methods to achieve the sustainable and economic development for human society. Molybdenum-based sepiolite (Mo/SEP) catalyst presented a promising performance for lignin depolymerization under supercritical ethanol (LDSE). Herein, the influence of reductive treatments for calcined Mo/SEP (C-Mo/SEP) catalyst on lignin depolymerization was systematically investigated under supercritical ethanol. Two reduced catalysts N-Mo/SEP an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…As shown in Figure , the Mo 3d doublet is contributed from a large amount of Mo 4+ , Mo 5+ , and Mo 6+ with the 3 d 5/2 bands located at 229.5, 230.8, and 232.7 eV, respectively. The Mo 5+ species formation can be caused by the conversion of MoO 3 to MoO x C y H z and/or oxygen vacancy (OV) produced by the MoO 3 reduction. , The Mo 5+ contents of the used catalysts in the solvents at 250 °C via the deconvolution of XRPES decrease in the order: E (51%) > M (46%) > IP (27%) > EA (25%) > H (1%). The Mo 5+ content of the used catalyst in H and EA increased dramatically to 53 and 55%, respectively, with raising temperature to 300 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…As shown in Figure , the Mo 3d doublet is contributed from a large amount of Mo 4+ , Mo 5+ , and Mo 6+ with the 3 d 5/2 bands located at 229.5, 230.8, and 232.7 eV, respectively. The Mo 5+ species formation can be caused by the conversion of MoO 3 to MoO x C y H z and/or oxygen vacancy (OV) produced by the MoO 3 reduction. , The Mo 5+ contents of the used catalysts in the solvents at 250 °C via the deconvolution of XRPES decrease in the order: E (51%) > M (46%) > IP (27%) > EA (25%) > H (1%). The Mo 5+ content of the used catalyst in H and EA increased dramatically to 53 and 55%, respectively, with raising temperature to 300 °C.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Various research groups have proposed several heterogeneous catalytic systems (noble or transition metals) for the selective cleavage of lignin and have been reviewed extensively. , However, the design of an appropriate catalyst is still far from ideal and continues to be a challenging topic of research. , Currently, the reported methodologies in the literature for lignin utilization are pyrolysis, , catalytic oxidative depolymerization, hydrogenolysis, , and acid–alkali hydrolysis . The procedure of hydrogenation can increase product stability considerably.…”
Section: Introductionmentioning
confidence: 99%
“…Under the influence of angle strain, Ar-OH bond fracture and alkyl group substitution were easily realized. Recently, based on the properties of molybdenum and sepiolite clay, our team prepared a series of sepiolite-supported Mo-based catalysts and investigated the effects of Mo content, reduction treatment, calcination temperature, and transition metal and nonmetal modification , on lignin depolymerization for liquid fuels and aromatic compounds. These results confirmed that the metal constituents, oxygen species, and surface functional groups (MoO, Mo–O) of Mo-based catalysts can be changed through the above-mentioned modification methods to achieve the regulation of the acid–base sites and electron-rich/electron-poor sites, which accordingly maximize the polarization of β-O-4 bonds, reduce the dissociation energy of C–O bonds, and produce more oxygen-containing phenolic intermediates.…”
Section: Introductionmentioning
confidence: 99%